Introducing Switching Ordered Statistic CFAR Type I in Different Radar Environments. (17th March 2009) - Erfanian Erfanian, Saeed Saeed; Tabataba Vakili Tabataba Vakili, Vahid Vahid
Abstract : In this paper, a new CFAR detector based on a switching algorithm and OS-CFAR for nonhomogeneous background environments is introduced. The new detector is named Switching Ordered Statistic CFAR type I (SOS CFAR I). The SOS CFAR I selects a set of suitable cells and then with the help of the ordering method, estimates the unknown background noise level. The proposed detector does not require any prior information about the background environment and uses cells with similar statistical specifications to estimate the background noise. The performance of SOS CFAR I is evaluated and compared with other detectors such as CA-CFAR, GO-CFAR, SO-CFAR, and OS-CFAR for the Swerling I target model in homogeneous and nonhomogeneous noise environments such as those with multiple interference and clutter edges. The results show that SOS CFAR I detectors considerably reduce the problem of excessive false alarm probability near clutter edges while maintaining good performance in other environments. Also, simulation results confirm the achievement of an optimum detection threshold in homogenous and nonhomogeneous radar environments by the mentioned processor.